Ion collection efficiency of ionization chambers in ultra‐high dose‐per‐pulse electron beams. Issue 2 (3rd January 2021) - Kranzer, Rafael; Poppinga, Daniela; Weidner, Jan; Schüller, Andreas; Hackel, Thomas; Looe, Hui Khee; Poppe, Björn
Abstract : Purpose: The ion collection efficiency of vented ionization chambers has been investigated in an ultra‐high dose‐per‐pulse (DPP) electron beam. The role of the chamber design and the electric field strength in the sensitive air volume have been evaluated. Methods: An advanced Markus chamber and three specially designed parallel plate air‐filled ionization chambers (EWC: End Window Chamber) with varying electrode distance of 0.5, 1, and 2 mm have been investigated. Their ion collection efficiencies were determined experimentally using two methods: extrapolation of Jaffé plots and comparison against a DPP‐independent reference detector. The latter was achieved by calibrating a current transformer against alanine dosimeters. All measurements were performed in a 24 MeV electron beam with DPP values between 0.01 and 3 Gy. Additionally, the numerical approach introduced by Gotz et al. was implemented taking into account space charge effects at these ultra‐high DPPs. The method has been extended to obtain time‐resolved and position‐dependent electric field distortions within the air cavity. Results: The ion collection efficiency of the investigated ionization chambers drops significantly in the ultra‐high DPP range. The extent of this drop is dependent on the electrode distance, the applied chamber voltage and thus the field strength in the sensitive air volume. For the Advanced Markus chamber, a good agreement between the experimental, numerical and the results of Petersson et al. could be shown. Using the three EWCs with different electrode spacing, an improvement of the ion collection efficiency and a reduction of the polarity effect with decreasing electrode distance could be demonstrated. Furthermore, the results revealed that the determination of the ion collection efficiency from the Jaffé plots and therefore also from two‐voltage method typically underestimate the ion collection efficiency in the region of high dose‐per‐pulse (3 to 130 mGy) and overestimate the ion collection efficiency at ultra‐high dose‐per‐pulse (>1 Gy per pulse). Conclusions: In this work, the ion collection efficiency determined with different methods and ionization chambers have been compared and discussed. As expected, an increase of the electric field in the ionization chamber, either by applying a higher bias voltage or a reduction of the electrode distance, improves the ion collection efficiency and also reduces the polarity effect. For the Advanced Markus chamber, the experimental results obtained by comparison against a reference agree well with the numerical solution. Based on these results, it seems possible to keep the recombination loss less than or equal to 5% up to a dose‐per‐pulse of 3 Gy with an appropriately designed ionization chamber, which corresponds to the level accepted in conventional radiotherapy dosimetry protocols.